Pesticide Spraying Practices and Hypertension Risk among farmers in Bumen Village, Indonesia - Masyithah, Wulan; Onny Setiani; Darundiati, Yusniar Hanani; Suhartono; Raharjo, Mursid; Hasim, Jamal Hisham (Poltekkes Kemenkes Surabaya, 2025)
This study investigated the association between pesticide spraying practices and hypertension in horticultural farmers in Bumen Village, Sumowono District, Indonesia. A cross-sectional study was conducted among 132 male farmers selected through purposive sampling. Data were collected through structured interviews, blood pressure measurements, and field observations. Logistic regression revealed that mixing ≥2 pesticide types (OR=4.828; p=0.028), spraying ≥4 times per week (OR=4.552; p=0.010), and incomplete PPE use (OR=3.551; p=0.015) were significantly associated with hypertension. These findings underscore the need for stricter pesticide regulation, improved PPE use, and regular health monitoring to reduce health risks among farmers.